New genera of Psocoptera (Insecta), from Mexico, Belize and Ecuador (Psoquillidae, Ptiloneuridae, Lachesillidae) - Aldrete, Alfonso N. García (Zootaxa, 2006)
Four new species of Psocoptera are described, each in a new monotypic genus: Rhyopsocoides typhicolus (Psoquillidae) and Omilneura circumvittata (Ptiloneuridae) from Mexico, Belicania cervantesi (Ptiloneuridae) from Belize, and Waoraniella erwini (Lachesillidae) from Ecuador. Relationships within each family are discussed, and keys to the genera in each family are included.